2017
DOI: 10.1007/s00125-017-4388-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical administration of DPP-IV inhibitors prevents retinal neurodegeneration in experimental diabetes

Abstract: Aims/hypothesis The main aims of the present study were: (1) to assess the expression and content of dipeptidyl peptidase IV (DPP-IV) in human and db/db mouse retinas, and in human vitreous fluid; and (2) to determine whether the topical administration of the DPP-IV inhibitors (DPP-IVi) would prevent retinal neurodegeneration and vascular leakage in db/db mice by reducing endogenous glucagon-like peptide 1 (GLP-1) degradation. Methods To assess the expression and content of DPP-IV, human samples of vitreous fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 41 publications
5
78
0
Order By: Relevance
“…Preclinical data demonstrated beneficial pleiotropic effects of incretin therapies on DR, independent of the glucose‐lowering effect resulting from reducing blood‐retinal barrier breakdown, inflammation and neuronal cell death . Topical administration of DPP‐4i was shown to prevent neurodegeneration and vascular leakage in db/db mice by enhancing GLP‐1 . The results in patients with T2DM remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data demonstrated beneficial pleiotropic effects of incretin therapies on DR, independent of the glucose‐lowering effect resulting from reducing blood‐retinal barrier breakdown, inflammation and neuronal cell death . Topical administration of DPP‐4i was shown to prevent neurodegeneration and vascular leakage in db/db mice by enhancing GLP‐1 . The results in patients with T2DM remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has important therapeutic implications. In this regard, neuroprotective effects have been reported by using insulin [55], PEDF [56, 57], somatostatin [58], GLP-1 [59, 60], dipeptidyl peptidase-IV (DPP-IV) inhibitors [61] and erythropoietin or erythropoietin-linked analogues [62, 63] in various experimental models. The European Consortium for the Early Treatment of Diabetic Retinopathy (EUROCONDOR) clinical trial has recently shown that topical administration of somatostatin arrested the progression of neurodysfunction as assessed by mfERG (implicit time) in participants with some degree of neurodysfunction at baseline [64].…”
Section: Is Neurodegeneration the Primary Event In The Pathogenesis Omentioning
confidence: 99%
“…To our knowledge, there are no published studies in which cell-specific defects in microvascular or neural cells result in a diabetic retinopathy-like phenotype. In addition, although several studies using neuroprotective drugs, such GLP-1 and DPP-IV inhibitors, have prevented vascular leakage in rodents [5961], it is unknown if this effect was due to neuroprotection or to direct vascular effects. In addition, recent results from the EUROCONDOR study showed that a significant proportion of individuals with type 2 diabetes present with early microvascular disease without detectable neurodysfunction [64, 80].…”
Section: How Do We Integrate the Microvascular And Neural Components?mentioning
confidence: 99%
“…However, the mechanistic pathways were not examined. Although it could be argued that eye drops can hardly reach the posterior chamber of the eye (i.e., the vitreous and the retina), this and other studies showed the contrary, and in fact, a lot of drugs are able to reach the retina in pharmacological concentrations, at least in animal models [27,28,29,30,31]. Furthermore, we used a new formulation based on liposomal citicoline, phospholipids, sodium hyaluronate, phosphate buffer, and water, in which liposomal systems would act as a penetration enhancer and to avoid the use of eye drop preservatives [24].…”
Section: Discussionmentioning
confidence: 90%